Kekerasan Atas Nama Agama: Perspektif Politik - Cornelis Lay (Jurnal Ilmu Sosial dan Ilmu Politik, 2009)
Violence is a political and sociological phenomena. It occurs either horizontally and vertically in many dimensions and characteristics. For years Indonesia has experienced various cases related to violence. Certain kind of violence, such as religion based violence, occurs more frequently and involving state and political interests. This paper discusses about the religion based violence phenomena and shows that religion is often used to justify the action and political interest of certain groups in Indonesia.